2022
DOI: 10.3390/su14148337
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Stoichiometry (C, N, P) of Soil in the Wetland Critical Zone of Dongting Lake, China: Understanding Soil C, N and P Status at Greater Depth

Abstract: Earth’s critical zone is defined as a plant–soil–water system, which covers a wide area and has a large vertical thickness, but the soil elemental stoichiometry characteristics of the critical zone at different depths are still unclear. In this study, the spatial distribution of soil carbon (C), nitrogen (N) and phosphorus (P) in the critical zone of a typical wetland in Dongting Lake, China, and their ecological chemometric characteristics were analyzed. The results indicated that: (1) the average C, N and P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…A study of two typical marsh wetlands showed that TN concentrations were highest in the surface sediment [32]. Wu et al (2022) studied the elemental stoichiometry of sediments in a wetland critical zone and found that nitrogen and phosphorus concentrations increased from the deep layers to the surface [33]. The high nitrogen and phosphorus concentrations in surface sediments may be related to plant litter decomposition, microbial activity, and sediment deposition.…”
Section: Distribution Of Sediment Nitrogen and Phosphorusmentioning
confidence: 99%
“…A study of two typical marsh wetlands showed that TN concentrations were highest in the surface sediment [32]. Wu et al (2022) studied the elemental stoichiometry of sediments in a wetland critical zone and found that nitrogen and phosphorus concentrations increased from the deep layers to the surface [33]. The high nitrogen and phosphorus concentrations in surface sediments may be related to plant litter decomposition, microbial activity, and sediment deposition.…”
Section: Distribution Of Sediment Nitrogen and Phosphorusmentioning
confidence: 99%